The Mediating Role of Work Motivation in the Relationship between Flextime and Lecturer Performance at Private Universities in Serang City, Banten - Chaidir, John; Zulfikar, Taufik; Aprianti, Ine; Saepul Millah, Fadli (Jurnal MS, 2025)
Objective: This study aims to examine the effect of work flexibility on lecturers’ performance, with work motivation as a mediating variable, in the context of private universities. The research seeks to determine whether flexible work arrangements can directly and indirectly enhance lecturers’ performance through increased motivation. Methodology: This quantitative survey involved all permanent lecturers actively teaching at 32 Private Universities (PTS) in Serang City, Banten, with an estimated population of 900 lecturers. A probability sampling strategy using stratified random sampling was employed, treating each university as a stratum, followed by proportional allocation and simple random selection within strata. The final sample comprised 369 respondents, exceeding the minimum requirement for PLS-SEM analysis based on Cohen’s guideline and G*Power calculations. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.4 to test both direct and mediating effects. Findings: The results demonstrate that work flexibility has a positive and significant effect on work motivation and lecturer performance. Work motivation also has a significant positive influence on lecturer performance and partially mediates the relationship between work flexibility and performance. Conclusion: Enhancing work flexibility is essential for improving both motivation and performance among lecturers in private universities. Universities are encouraged to adopt flexible work arrangements that maintain academic productivity while supporting work-life balance. Keyword: Work Flexibility, Work Motivation, and Lecturers’ Performance